Desire - Székely, János 1901-1958; Stemmle, Robert Adolf 1903-1974; Hollaender, Friedrich 1896-1976 (Universal Studios, 2023)
"Eine elegante, verführerische Hochstaplerin und Juwelendiebin benutzt einen jungenhaft unbekümmerten Amerikaner, um eine sehr kostbare Perlenkette, die sie sich erschwindelt hat, aus Frankreich über die spanische Grenze zu ihrem Komplizen zu schmuggeln. Charmante Komödie mit guten Darstellern und witzigen Dialogen, deren Spiel um Schein und Sein von Auslassungen und Ellipsen lebt. [...]" [filmdienst.de]
Original: USA 1936
Indicator limited edition special features: 2022 restoration from a 4K scan ; original mono audio ; audio commentary with writer and critic Nathaniel Bell and film historian David Del Valle (2021) ; Frank Borzage oral history (1958, 40 mins): rare archival audio recording of the filmmaker in conversation with George Pratt ; Mr Cooper goes to Hollywood (2023, 12 mins): film historian and curator Nathalie Morris discusses the stardom and style of iconic Hollywood actor Gary Cooper ; Lux Radio Theatre: ‘Desire’ (1937, 55 mins): radio play adaptation of the film’s screenplay, starring Marlene Dietrich alongside Herbert Marshall in the Gary Cooper role ; original theatrical trailer ; image gallery: promotional and publicity materials ; new and improved English subtitles for the deaf and hard of hearing ; limited edition exclusive 36-page booklet with a new essay by Christina Newland, archival interviews with Gary Cooper, Marlene Dietrich, and Frank Borzage, and film credits ; UK premiere on Blu-ray ; limited edition of 3,000 copies for the UK
Bildformat 1.37:1
Keywords: Film; Blu-Ray-Disc